2012
DOI: 10.1155/2012/231502
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Serum Paraoxonase Activities are Characteristic of Metabolic Syndrome and May Influence the Metabolic-Syndrome-Related Risk of Coronary Artery Disease

Abstract: Low concentrations of plasma high-density lipoprotein (HDLs) are characteristic in metabolic syndrome (MS). The antioxidant ability of HDLs is, at least in part, attributable to pleiotropic serum paraoxonase (PON1). Different PON1 activities have been assessed in 293 subjects with (n = 88) or without MS (n = 205) and with (n = 195) or without (n = 98) angiographically proven coronary artery disease (CAD). MS subjects had low PON1 activities, with a progressively decreasing trend by increasing the number of MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
4
16
0
2
Order By: Relevance
“…For example, a cross-sectional study in more than 7,000 ostensibly-healthy volunteers showed that individuals with high serum ferritin concentrations had a higher predisposition to metabolic syndrome ( 42 ). Importantly, serum PON1 activity is decreased in metabolic syndrome ( 26,43 ), and such impairment has been reported to increase the risk of developing cardiovascular disease ( 26 ). Another fi nding of the present study is the higher frequency of patients homozygous for the R alloform of the PON1 192 polymorphism being associated with HH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a cross-sectional study in more than 7,000 ostensibly-healthy volunteers showed that individuals with high serum ferritin concentrations had a higher predisposition to metabolic syndrome ( 42 ). Importantly, serum PON1 activity is decreased in metabolic syndrome ( 26,43 ), and such impairment has been reported to increase the risk of developing cardiovascular disease ( 26 ). Another fi nding of the present study is the higher frequency of patients homozygous for the R alloform of the PON1 192 polymorphism being associated with HH.…”
Section: Discussionmentioning
confidence: 99%
“…Serum PON1 TBBLase and DEPCyMCase activities were analyzed as previously reported ( 19,(24)(25)(26). Serum markers of iron metabolism, as well as other common biochemical parameters, were measured by standard methods in a RXL Dimension automated analyzer (Dade International Inc., Newark, DE).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…All three isoforms have been implicated as candidate genes for atherosclerosis and cardiovascular diseases due to their ability to attenuate lipid peroxidation, and due to their antioxidant and antiatherogenic effects [15-17]. Low levels of PON activity are thought to increase the risk of atherosclerosis [18], and thereby contribute to a predisposition towards stroke, coronary artery disease (CAD) and vascular disorders in diabetes [19-21]. Other studies have demonstrated a positive association between single nucleotide polymorphisms (SNPs) in PON genes and stroke susceptibility [22-25], although conflicting results have been seen in different ethnic groups [26-28].…”
Section: Introductionmentioning
confidence: 99%
“…Other abnormalities in HDL could contribute in reducing their beneficial effects on the endothelium. Patients with metabolic syndrome have reduced paraoxonase (PON-1) levels and activity [34], an enzyme recently suggested to play a role in eNOS activation [28], and reduced HDL antioxidant capacity [35]. The present findings indicate that treatment with fenofibrate and niacin completely restores the impaired HDL-mediated endothelial protection in patients with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 51%